STUDY OF LOADING AND OPERATIONAL MODE OF TRANSMISSION OF TRACTOR CLASS 14 KN WITH SYSTEM OF TRANSVERSE BLOCKING - Левчук, В. І.; Лихвенко, С. П. (Scientific Progress & Innovations, 2017)
The results of experimental research work as part of an arable unit MTZ-80 with mounted plow PN-3-35 on sandy loam soil in Belarus in the differential and locked rear axle of cross-axle drive in acceleration mode with a deep plow on the go and pre-recessed plow. Using strain gauges, the torque on the clutch shaft and the axles of the tractor rear axle. An analysis of average and peak values ​​of moments we found that when a blocked drive total points on the semi-axes were 5,9–31,3 % more than the differential drive. Over-loaded on all test conditions was the right half. Maximum points on it were greater than on the left on 4,6–20,3 % at lock off and 12,1–32,5 % when enabled. The calculations of the strength of the semi-axes tractor for peak and average load were completed. Research loads on the primary and secondary shafts of the tractor gearbox bearing blocks have not found a significant effect of the differential lock on the load.